Pengaruh Problem Based Learning Berbantuan Media Colors By Numbers Terhadap Kemampuan Berhitung Siswa Sekolah Dasar - Vitaloka, Affra Brilliant; Rukmana, Diki (BRILIANT: Jurnal Riset dan Konseptual, 2025)
Mathematics subjects with the development of numeracy skills are two inseparable things because numeracy skills encourage students to develop critical, logical and creative thinking. The ability to count also has great relevance in students' lives because it is directly related to everyday situations. However, there is a problem faced by students at SDN Kramat 06, namely their lack of numeracy skills. Through field observations, there are findings that show that numeracy skills at SDN Kramat 06 are still relatively low. This is shown in the learning outcomes and oral test scores carried out in class which are still relatively low. This situation is because the use of conventional learning models makes students passive and the teacher is too dominant so that students can only listen to the explanation given. The selection of the Problem Based Learning Model assisted by Colors by Numbers media is expected to improve students' numeracy skills. The results of statistical analysis show that the Problem Based Learning model assisted by Colors by Numbers media makes changes to improving the numeracy skills of class IV students at SDN Kramat 06. This is reflected in the results of the experimental class achieving better numeracy skills than the control class and the use of the Problem Based Learning model with the help of Colors by Numbers media has a significant effect on the numeracy skills of class IV students at SDN Kramat 06.